On a destructive pendant cloud at Bamrauli - RAO, D.VENKATESWARA; SEN, BIJAY BHUSAN (MAUSAM, 1958)
The meteorological conditions leading to the appearance of a balloon-shaped Fendant cloud at Bamrauli at 1255 IST on 14 September 1956 have been investigated. The nature of the destruction wrought by this cloud is described and discussed.